Pengembangan Manajemen Risiko Dalam Rangka Membangun Sistem Peringatan Dini (Studi Kasus “Carrefour Indonesia”) - Irsan, Muhammad Syah (Jurnal Ilmu Ekonomi dan Sosial (JIES), 2021)
This thesis deals with the application of the risk management Program at the "Carrefour Indonesia" to face the threat and/or risk that have impact on the continuity of the business of the company; both coming from internal and external such as: regulation, competition, markets, mergers and acquisitions, resources, and others in order to provide early warning for the company in taking overall mitigation of the threat and/or risk. This study was made in the form of case studies; aiming to gain deep understanding of risk management, intelligence and early warning systems Results of the research showed that "Carrefour Indonesia" risk triggered by the strategy to be implemented in the future and the application of the risk management Program at the "Carrefour Indonesia" has not been fullest in giving early warning to the company, so it needed improvements on the system, the resources and the corporate structure so that early warning systems can be integrated with risk management.